Impact of general anaesthesia on breast cancer survival: a 5-year follow up of a pragmatic, randomised, controlled trial, the CAN-study, comparing propofol and sevofluraneResearch in context - Mats Enlund; Anders Berglund; Anna Enlund; Johan Lundberg; Fredrik Wärnberg; Dong-Xin Wang; Andreas Ekman; Rebecca Ahlstrand; Per Flisberg; Lars Hedlund; Ingrid Östlund; Leif Bergkvist (EClinicalMedicine, 2023)
Summary: Background: Anaesthesia may impact long-term cancer survival. In the Cancer and Anaesthesia study, we hypothesised that the hypnotic drug propofol will have an advantage of at least five percentage points in five-year survival over the inhalational anaesthetic sevoflurane for breast cancer surgery. Methods: From 2118 eligible breast cancer patients scheduled for primary curable, invasive breast cancer surgery, 1764 were recruited after ethical approval and individual informed consent to this open label, single-blind, randomised trial at four county- and three university hospitals in Sweden and one Chinese university hospital. Of surveyed patients, 354 were excluded, mainly due to refusal to participate. Patients were randomised by computer at the monitoring organisation to general anaesthesia maintenance with either intravenous propofol or inhaled sevoflurane in a 1:1 ratio in permuted blocks. Data related to anaesthesia, surgery, oncology, and demographics were registered. The primary endpoint was five-year overall survival. Data are presented as Kaplan-Meier survival curves and Hazard Ratios based on Cox univariable regression analyses by both intention-to-treat and per-protocol. EudraCT, 2013-002380-25 and ClinicalTrials.gov, NCT01975064. Findings: Of 1764 patients, included from December 3, 2013, to September 29, 2017, 1670 remained for analysis. The numbers who survived at least five years were 773/841 (91.9% (95% CI 90.1–93.8)) in the propofol group and 764/829 (92.2% (90.3–94.0)) in the sevoflurane group, (HR 1.03 (0.73–1.44); P = 0.875); the corresponding results in the per-protocol-analysis were: 733/798 (91.9% (90.0–93.8)) and 653/710 (92.0% (90.0–94.0)) (HR = 1.01 (0.71–1.44); P = 0.955). Survival after a median follow-up of 76.7 months did not indicate any difference between the groups (HR 0.97, 0.72–1.29; P = 0.829, log rank test). Interpretation: No difference in overall survival was found between general anaesthesia with propofol or sevoflurane for breast cancer surgery. Funding: Swedish Research Council; Uppsala-Örebro Regional Research Council; Västmanland Regional Research Fund; Västmanland Cancer Foundation; Stig and Ragna Gohrton Foundation; Birgit and Henry Knutsson Foundation.